The answer is 2x-3, you multiply the x value by 2 and then subtract 3 which gives you your y value
Answer:f(4)=−3x−1 f ( 4 ) = - 3 x - 1.
Step-by-step explanation:ff(4)=−3x−1 f ( 4 ) = - 3 x - 1.
f(4)=−3x−1 f ( 4 ) = - 3 x - 1. Replace the variable x x with 4 4 in the expression. f(4)=−3⋅4−1 f ( 4 ) = - 3 ⋅ 4 - 1. Simplify the result.
7, 14 would be it but you have to divide the whole equation by 2 to get the y alone
Answer:
Yes, they are equal.
Step-by-step explanation:
-3.0 + 0.8 = -2.2
<em>Hope</em><em> </em><em>it</em><em> </em><em>helps</em><em>.</em>